COMPARING SENGON (Paraserianthes falcataria) CULTIVATIONS AT DEGRADED LAND OF KALIMANTAN - Wahyudi, Wahyudi (Journal of Agroecology, 2015)
Forest degradation in Indonesia is nearly 21,9 million ha. Effort to rehabilitate those forests is always constrained by funding availability, social problems and land fertility. The aim of this research was to compare the agroforestry (mixture of Paraserianthes falcataria and paddy), intensive monoculture and conventional monocultural systems. This research consisted of three treatments each treatment consisted of 10 plots. Data were analysed using homogeneity test, ANOVA, and LSD test using SPSS 19.0. Research was conducted in forest region in Lamida Village, Balangan District, South Kalimantan Province for the period of 2 years. Research result showed that at the first years, mean annual increment (MAI) of Paraserianthes falcataria in agroforestry system was 3.45cm in diameter and 3.66 min height as good as with intensive monocultural system of 3.21cm in diameter and 3.25 min height, whereas conventional monocultural system was 1.99cm in diameter and 1.75 min height only, which was significantly differentat 0.05 level from the first and second treatment. Agroforestry system also produced mount-paddy of 3.01 ton ha-1 in the first year and 2.98 ton ha-1 in the second year. Agroforestry system is the best system because beside it produces better growth for Paraserianthes falcataria, as good as, intensive monocultural system, this plantation system also creates vocation and improves social welfare.